Temporal evolution of two auroral arcs as measured by the Cluster satellite and coordinated ground-based instruments - A. T. Aikio; K. Mursula; S. Buchert; F. Forme; O. Amm; G. Marklund; M. Dunlop; D. Fontaine; A. Vaivads; A. Fazakerley (Annales Geophysicae, 2004)
The four Cluster s/c passed over Northern Scandinavia on 6 February 2001 from south-east to north-west at a radial distance of about 4.4 R E in the post-midnight sector. When mapped along geomagnetic field lines, the separation of the spacecraft in the ionosphere was confined to within 110km in latitude and 50km in longitude. This constellation allowed us to study the temporal evolution of plasma with a time scale of a few minutes. Ground-based instrumentation used involved two all-sky cameras, magnetometers and the EISCAT radar. The main findings were as follows. Two auroral arcs were located close to the equatorward and poleward edge of a large-scale density cavity, respectively. These arcs showed a different kind of a temporal evolution. (1) As a response to a pseudo-breakup onset, both the up- and downward field-aligned current (FAC) sheets associated with the equatorward arc widened and the total amount of FAC doubled in a time scale of 1–2min. (2) In the poleward arc, a density cavity formed in the ionosphere in the return (downward) current region. As a result of ionospheric feedback, a strongly enhanced ionospheric southward electric field developed in the region of decreased Pedersen conductance. Furthermore, the acceleration potential of ionospheric electrons, carrying the return current, increased from 200 to 1000eV in 70s, and the return current region widened in order to supply a constant amount of return current to the arc current circuit. Evidence of local acceleration of the electron population by dispersive Alfvén waves was obtained in the upward FAC region of the poleward arc. However, the downward accelerated suprathermal electrons must be further energised below Cluster in order to be able to produce the observed visible aurora. Both of the auroral arcs were associated with broad-band ULF/ELF (BBELF) waves, but they were highly localised in space and time. The most intense BBELF waves were confined typically to the return current regions adjacent to the visual arc, but in one case also to a ...